2017
DOI: 10.1149/2.1211707jes
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Film Growth Study of the Corrosion of Magnesium Alloys AZ31B and ZE10A in 0.01% NaCl Solution

Abstract: A sequential isotopic tracer study of corrosion film growth for Mg-3Al-1Zn-0.25Mn (AZ31B) and Mg-1.2Zn-0.25Zr-<0.5Nd (ZE10A) was conducted by 4 h immersion in H 2 18 O or D 2 16 O, followed by a 20 h immersion in a 0.01 wt% NaCl H 2 18 O or D 2 16 O solution. Sputter depth profiles were obtained for 16 O, 18 O, H, and D using secondary ion mass spectrometry (SIMS). Compared to the previous tracer study for these alloys in salt-free water, the addition of 0.01 wt% NaCl resulted in a transition from oxygen inw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 74 publications
(258 reference statements)
3
10
0
Order By: Relevance
“…From experiments carried out in pure water, it was concluded that the Fe-containing Zr particles acted as local cathode sites during the corrosion of E717 alloy. Others have studied the influence of chloride ions concentration on the properties of the surface film formed on E717 under immersion conditions 19,20 .In comparison to a dense bilayered film, consisting of an inner MgO layer and an outer Mg(OH)2 film formed in water, the presence of high Clconcentration produces a significantly thicker, nano porous outer layer 19 . Chloride ion penetration into the inner MgO-base layer was detected at high concentrations of ≥ 1% w/v by using a combination of SEM and STEM, but not after immersion in more dilute concentration of 0.01 % w/v 20 , although the authors report a different growth mechanism within the dense MgO base layer.…”
Section: Introductionmentioning
confidence: 99%
“…From experiments carried out in pure water, it was concluded that the Fe-containing Zr particles acted as local cathode sites during the corrosion of E717 alloy. Others have studied the influence of chloride ions concentration on the properties of the surface film formed on E717 under immersion conditions 19,20 .In comparison to a dense bilayered film, consisting of an inner MgO layer and an outer Mg(OH)2 film formed in water, the presence of high Clconcentration produces a significantly thicker, nano porous outer layer 19 . Chloride ion penetration into the inner MgO-base layer was detected at high concentrations of ≥ 1% w/v by using a combination of SEM and STEM, but not after immersion in more dilute concentration of 0.01 % w/v 20 , although the authors report a different growth mechanism within the dense MgO base layer.…”
Section: Introductionmentioning
confidence: 99%
“…21 The authors considered a two-phase medium: solid metal and liquid electrolyte. Inspired by experimental observations that show gradual changes in the alloy composition and mechanical properties from the bulk to the surface, in a partially corroded layer at corrosion front, [29][30][31][32][33] they introduced an effective diffusion in the solid that represents both the dissolution of metal and the out-diffusion of ions into the electrolyte. Assuming that regular diffusion in the liquid governs the movement of ions in the electrolyte, they solved a single diffusion equation over the two-phase material, with different diffusion coefficients depending on the phase.…”
Section: Review Of Peridynamic Corrosion Modelmentioning
confidence: 99%
“…The alloying element Ca might have different effect on the microstructure, and hence the resulting PEO film of the Mg–Al–Zn alloys as compared to that of the Mg–Al–Mn alloys. The development of an Mg based-biodegradable implant included Zn as alloying element to improve its mechanical strength [25,26,27]. This work aims to throw light on explaining the corrosion behavior and apatite-forming ability of the coatings formed on the Mg–6Al–1Zn–xCa alloys as a result of alteration in the microstructure with a variation of Ca content.…”
Section: Introductionmentioning
confidence: 99%